Isolated trochlear nerve palsy: case report and modern considerations - Anna N. Belova; Gennadii E. Sheiko; Vera N. Grigoryeva; Evgenij A. Kliuev; Marina V. Rasteryaeva (LLC "MEDIAFORMAT", 2024)
Neurologically isolated trochlear nerve (TN) injury is uncommon. We describe the case of acute vertical diplopia development in a 64-year-old man who considered himself healthy. The cause of diplopia was neuropathy of TN. The diagnostic search gave reason to assume that TN damage was associated with microangiopathy caused by arterial hypertension and dyslipidemia newly diagnosed in the patient. A diagnostic algorithm for acute vertical diplopia and the range of diseases for differentiation with isolated TN neuropathy are discussed, as well as the prognosis and patient's management. The association of isolated TN neuropathy with migraine and the risk of ischemic stroke is considered.